The Effects of Digital Transformation on Healthcare Business Models in Zimbabwe: Perceptions and Implications - Mataba, Augustine Torayi; Chibaro, Munyaradzi (European Journal of Information and Knowledge Management, 2024)
Purpose: This study explores the effects of digital transformation on healthcare business models in Zimbabwe, focusing on the perceptions and implications among healthcare professionals. The purpose of this research is to understand how digital technologies influence healthcare service delivery, patient outcomes, and organizational sustainability within the Zimbabwean context. Methodology: Utilizing a mixed-methods approach, the study involved a population of 100 healthcare professionals from which a sample of 80 participants was selected through both probability and non-probability sampling techniques. Probability sampling provided a representative sample, while non-probability sampling offered targeted insights. Findings: The findings indicate that digital transformation significantly enhances efficiency, accessibility, and the quality of healthcare services. Specifically, the integration of digital technologies has led to improved patient engagement, streamlined processes, and enhanced decision-making within healthcare organizations. Unique Contribution to Theory, Practice and Policy: This study's unique contribution lies in its comprehensive empirical analysis of digital transformation's impact on healthcare business models in Zimbabwe, filling a notable gap in existing literature. The research provides valuable insights into how digital tools can reshape healthcare practices and business strategies. Based on these findings, the study recommends several actions for stakeholders in Zimbabwe's healthcare sector: policymakers should prioritize investments in digital infrastructure to ensure equitable access to technology across all healthcare facilities; healthcare organizations should foster a culture of innovation and implement training programs to enhance digital skills among professionals; and promoting collaborations between the public and private sectors is crucial to maximize resources and expertise in adopting digital solutions. These recommendations are designed to guide policy and practice in leveraging digital transformation to improve healthcare outcomes in Zimbabwe.